How effective is sun salutation in improving muscle strength, general body endurance and body composition? - Bhutkar, M. V.; Bhutkar, P. M.; Taware, G. B.; Surd, A. D. (Asian Journal of Sports Medicine, 2011)
Purpose: The purpose of the present study was to evaluate effects of regular practice of sun salutation on muscle strength, general body endurance and body composition. Methods: Subjects (49 male and 30 female) performed 24 cycles of sun salutation, 6 days a week for 24 weeks. Upper body muscle strength was determined by 1 repetition maximum (1RM) for bench press and shoulder press technique. Back and leg dynamometry was used to assess strength of back and leg muscles. General body endurance was evaluated by push-up and sit-up tests. Body composition was assessed by noting % body fat by using bioelectric impedance analysis. Perceived intensity of exercise by subjects was noted by Borg scale. Results: Muscle strength by bench press showed significant increase in male (29.49±9.70 to 36.12±9.09 Kg, P<0.001) and female (10.5±4.42 to 13.16±4.44 Kg, P<0.001) subjects. Strength by shoulder press also increased (males; 22.96±9.57 Kg to 26.53±11.05 Kg, P<0.001, females; 6.83±2.78 to 8.83±3.87, P<0.001). Endurance by push-ups & sit-ups showed similar findings in male (19.0±9.58 to 21.98±8.98, P < 0.001 and 24.92±10.41 to 29.84±12.64, p <0.001 respectively) and female (14.66±6.80 to 18.56±6.97 and 13.16±7.75 to 19.23±8.25, P<0.001 respectively) subjects. A significant decrease in body fat percent was observed only in female (27.68±5.46 to 25.76±4.72, P<0.001) but not in male subjects. BMI significantly decreased in both the groups (z=4.37, P<001 and t=5.41, P<0.001 respectively). Conclusion: From our observations we conclude that sun salutation can be an ideal exercise to keep oneself in optimum level of fitness.